2006
DOI: 10.1158/1535-7163.mct-06-0318
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 5-lipoxygenase by MK886 augments the antitumor activity of celecoxib in human colon cancer cells

Abstract: Cyclooxygenase (COX)-2 and 5-lipoxygenase (5-LOX) are key enzymes involved in arachidonic acid metabolism. Their products, prostaglandins and leukotrienes, are involved in colorectal tumor development. We aimed at evaluating whether combined blocking of the COX-2 and 5-LOX pathways might have additive antitumor effects in colorectal cancer. The expression/activity of COX-2 and 5-LOX were assessed in 24 human colorectal cancer specimens. The effects of the COX-2 inhibitor celecoxib and the 5-LOX inhibitor MK886… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 44 publications
2
73
1
Order By: Relevance
“…The total protein for the lung samples were obtained as described previously [31]. Lung tissues were lysed with buffer containing 0.9% NaCl, 20 mmol/L Tris-HCl (pH 7.6), 0.1% Triton X-100, 1 mmol/L phenylmethylsulfonyl fluoride, and 0.01% leupeptin, and homogenized.…”
Section: Western Blot Analysis For H 4 R and Cox-2 Protein Expressionmentioning
confidence: 99%
“…The total protein for the lung samples were obtained as described previously [31]. Lung tissues were lysed with buffer containing 0.9% NaCl, 20 mmol/L Tris-HCl (pH 7.6), 0.1% Triton X-100, 1 mmol/L phenylmethylsulfonyl fluoride, and 0.01% leupeptin, and homogenized.…”
Section: Western Blot Analysis For H 4 R and Cox-2 Protein Expressionmentioning
confidence: 99%
“…Furthermore, omega-3 supplementation was reported to significantly reduce synthesis of pro-inflammatory 5-LOX metabolites LTA 4 and lipid peroxides, thereby inhibiting IL-1β and TNF-α release [156]. shown to have additive effects in colon cancer cells [157].…”
Section: Influence Of Dietary Fats On Aa Cascadementioning
confidence: 99%
“…Cianchi et al [53] reported that the two major metabolic pathways of the AA cascade, COX and 5-LOX, are simultaneously up-regulated in human colorectal cancer.…”
Section: Role Of Eicosanoids In the Control Of Intestinal Epithelial mentioning
confidence: 99%